2018
DOI: 10.1177/0265407518798499
|View full text |Cite
|
Sign up to set email alerts
|

Family functioning and psychological outcomes in emerging adulthood: Savoring positive experiences as a mediating mechanism

Abstract: The present study tested the mediating role of perceived capability of savoring positive experiences in the associations between family functioning and emerging adults’ psychological outcomes, namely, depressive symptoms and life satisfaction. A sample of 167 Chinese emerging adults (112 female) were recruited from two major universities in Hong Kong. Participants were asked to complete a set of self-reported questionnaires. Findings based on structural equation modeling indicated that family functioning and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 83 publications
5
23
1
Order By: Relevance
“…Savoring could importantly influence many aspects of psychological functioning. In general, perceived capability of savoring has been found to be positively associated with state happiness, life satisfaction, and self-esteem, while it is inversely associated with depression, neuroticism, and hopelessness (Cheung et al, 2019;Gentzler, Palmer, & Ramsey, 2016;Quoidbach et al, 2015;Samios & Khatri, 2019;Smith & Hollinger-Smith, 2015). Among these three temporal components of savoring, perceived ability to savoring the moment has the strongest association with psychological outcomes compared to the other two temporal domains (Bryant, 2003).…”
Section: Savoringmentioning
confidence: 98%
See 2 more Smart Citations
“…Savoring could importantly influence many aspects of psychological functioning. In general, perceived capability of savoring has been found to be positively associated with state happiness, life satisfaction, and self-esteem, while it is inversely associated with depression, neuroticism, and hopelessness (Cheung et al, 2019;Gentzler, Palmer, & Ramsey, 2016;Quoidbach et al, 2015;Samios & Khatri, 2019;Smith & Hollinger-Smith, 2015). Among these three temporal components of savoring, perceived ability to savoring the moment has the strongest association with psychological outcomes compared to the other two temporal domains (Bryant, 2003).…”
Section: Savoringmentioning
confidence: 98%
“…A handful of recent cross-sectional studies have reported the associations of savoring and positive rumination with psychological well-being (Cheung et al, 2019;Kiken et al, 2017;Kraiss et al, 2019;Young et al, 2019). Although some studies have adopted longitudinal or experimental designs (Gomez-Baya et al, 2018;Olofsson et al, 2016;Rueschkamp et al, 2018), they did not contextualise the association of savoring and positive rumination with emotions within the daily events (i.e.…”
Section: Moderation Effects Of Savoring and Positive Rumination On Evmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, besides studies showing a direct relationship between family functioning and life satisfaction, there is some evidence that there can also be an indirect effect of family functioning on life satisfaction through healthpromoting behaviors, 19 personal growth, 31 romantic attachment, 32 stress resistance, 31 savoring positive experiences, 33 positive coping styles, and perceived social support. 34 Although there are no studies specifically targeting emotional intelligence and its role in the relationship between family functioning and life satisfaction, the existing literature suggests that such an effect is plausible.…”
Section: Introductionmentioning
confidence: 99%
“…Parents who frequently demonstrate hostile and hurtful emotions may model their dysregulated behaviors for their young children to imitate [13]. Such dynamics are salient from childhood to emerging adulthood, particularly in the Chinese context [14], where filial obligations and interpersonal harmony are highly valued [15,16]. Notably, common Chinese proverbs, such as 家和萬事興 (“All affairs prosper in harmonious families”), emphasize the importance of cultivating family harmony.…”
Section: Introductionmentioning
confidence: 99%